Enhancing Veteran Engagement, Demonstrating Value and Supporting Oncology Team Wellness: One Service Delivery Model of Integrating Health Psychology Services in VA Oncology Care - Bloor, Lindsey E.; Tsao, Phoebe A.; Yentz, Sarah E.; Radhakrishnan, Archana; Choi, Enid; Ramnath, Nithya (Archives of Clinical and Biomedical Research, 2024)
Interdisciplinary team-based oncology care, that includes health psychology services, seeks to address mental health, health behaviors and psychosocial factors including distress that contribute to disease. This service delivery model paper describes the approach taken in one VA healthcare system, outlining broad and adaptive health psychology services in oncology that include direct, Veteran-centered, co-located care, assessment of value, and healthcare team well-being. We describe why and how this approach for direct clinical care is bio-psychosociallydriven, and aims to reach a broader range of the Veteran population, including Veterans coping with co-occurring mental health. We next offer clinical information that illuminates the utility of this approach, specifically descriptive statistics and perceptions from referring clinicians and Veterans. Lastly, we describe investment in this interdisciplinary healthcare team’s well-being and how this effort is foundational to the approach’s success and sustainment, as well as the team’s effort to continually improve cancer care services.